2021
DOI: 10.1108/ijwhm-08-2020-0136
|View full text |Cite
|
Sign up to set email alerts
|

Line managers' middle-levelness and driving proactive behaviors in organizational interventions

Abstract: PurposeThis paper explores line managers' proactive work behaviors in organizational interventions and ascertains how their management of their middle-levelness by aligning with the intervention, or not, influences their proactive work behaviors.Design/methodology/approachThe authors’ findings are based on thematic analysis of 20 semi-structured interviews of university heads of departments responsible for managing organizational interventions.FindingsThe authors found that line managers engaged in a range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…This result revealed that managerial support holds a pivotal role, mainly when action plans are underutilised, corroborating findings from prior research (e.g. Christensen et al , 2019; Helland et al , 2021; Nielsen et al , 2023). These effects were prominent at lower levels of action plan implementation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result revealed that managerial support holds a pivotal role, mainly when action plans are underutilised, corroborating findings from prior research (e.g. Christensen et al , 2019; Helland et al , 2021; Nielsen et al , 2023). These effects were prominent at lower levels of action plan implementation.…”
Section: Discussionsupporting
confidence: 90%
“…One important contextual factor that positively affects workplace interventions’ effectiveness is manager support (Christensen et al , 2019; Helland et al , 2021). Manager support can be defined as the extent to which the immediate manager of a team looks after their team members, asking whether team members have problems at work, helping to make team members’ work more manageable and listening to team members when they have issues (Holton et al , 2000).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As evident in prior research, a lack of support from senior managers makes it difficult for line managers to implement organizational interventions (Nielsen et al , 2017; Kossek et al , 2006). Recent studies conclude that it is essential that senior management and HR be committed in the preparation phase of an intervention and that all actors share an understanding of the goal of the intervention (Helland et al , 2021). Consequently, the strategic HR function in health-care organizations must articulate the necessity of the intervention to higher decision-makers so that line managers are provided with sufficient and appropriate resources, tools, instructions and authority to take the necessary actions.…”
Section: Discussionmentioning
confidence: 99%
“…The OD team must deeply understand governmental objectives and the associated departmental performance implications. (Helland et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This also includes the identification of the different causes and effects relating to the identified business problem and the interrelationships between these causes and effects. Helland et al (2021) raise an important point: senior management and the HR practitioner must be aware of the extent to which middle managers believe in the validity of an OD intervention and the evaluation of such interventions. According to Helland et al (2021:589), the attitude of middle management directly impacts the implementation of OD interventions.…”
Section: Diagnosis and Evaluationmentioning
confidence: 99%